2019
DOI: 10.15252/emmm.201809561
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proteasome rescues a pathogenic variant of respiratory chain assembly factor COA7

Abstract: Nuclear and mitochondrial genome mutations lead to various mitochondrial diseases, many of which affect the mitochondrial respiratory chain. The proteome of the intermembrane space ( IMS ) of mitochondria consists of several important assembly factors that participate in the biogenesis of mitochondrial respiratory chain complexes. The present study comprehensively analyzed a recently identified IMS protein cytochrome c oxidase assembly factor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 74 publications
5
65
0
Order By: Relevance
“…For further investigation of cytosolic translational responses under conditions of long-term mitochondrial stress, we silenced MIA40 for 72 h. The oxidoreductase MIA40 is responsible for the import of proteins into the intermembrane space of mitochondria (Chacinska et al , 2004). MIA40 also plays an important role in the biogenesis of respiratory chain complex enzymes in mitochondria (Longen et al , 2009; Mohanraj et al , 2019). The knockdown of MIA40 had an effect similar to that of treating the cells with menadione or rotenone for 48 h, but in HeLa cells, protein synthesis and expression of ATF4 were decreased (Figure 6, C and D; Supplemental Figure 6, A and B); however, ROS production and ATP levels were not significantly changed (Figure 6, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…For further investigation of cytosolic translational responses under conditions of long-term mitochondrial stress, we silenced MIA40 for 72 h. The oxidoreductase MIA40 is responsible for the import of proteins into the intermembrane space of mitochondria (Chacinska et al , 2004). MIA40 also plays an important role in the biogenesis of respiratory chain complex enzymes in mitochondria (Longen et al , 2009; Mohanraj et al , 2019). The knockdown of MIA40 had an effect similar to that of treating the cells with menadione or rotenone for 48 h, but in HeLa cells, protein synthesis and expression of ATF4 were decreased (Figure 6, C and D; Supplemental Figure 6, A and B); however, ROS production and ATP levels were not significantly changed (Figure 6, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Endoplasmic Reticulum stress has been reported to stimulate SC-formation (Balsa et al, 2019). Proteasome inhibition protects RC-assembly factor COA7 from degradation and improves CIV function in models of mitochondrial leukoencephalopathy (Mohanraj et al, 2019). Our data also suggests that triggering iSRC by mild proteostasis stress may offer an opportunity to ameliorate OxPhos-deficiency in mitochondrial diseases.…”
Section: Discussionmentioning
confidence: 53%
“…COA7 variants were not completely impaired in IMS import and folding, but their import and folding was strongly slowed down. Preventing cytosolic degradation via pharmacological inhibition of the proteasome thus not only increased cellular COA7 mutant levels, but also enabled mitochondrial import of COA7 variants, and restored complex IV activity and supercomplex formation (Mohanraj et al , ; Fig ).…”
Section: The Proteasome Controls Disulfide Relay‐mediated Protein Impmentioning
confidence: 99%
“…In the current issue of EMBO Molecular Medicine, Mohanraj et al (2019) identified cytochrome c oxidase assembly factor 7 (COA7) as a novel non-conventional disulfide relay substrate. Cytochrome c oxidase assembly factor 7 is involved in the assembly of complex IV (Kozjak-Pavlovic et al, 2014).…”
Section: Markus Habich and Jan Riemermentioning
confidence: 99%